2017
DOI: 10.1128/mbio.01861-17
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Quorum Sensing Circuitry of Burkholderia thailandensis Is Both Hierarchically and Homeostatically Organized

Abstract: The genome of the bacterium Burkholderia thailandensis encodes three complete LuxI/LuxR-type quorum sensing (QS) systems: BtaI1/BtaR1 (QS-1), BtaI2/BtaR2 (QS-2), and BtaI3/BtaR3 (QS-3). The LuxR-type transcriptional regulators BtaR1, BtaR2, and BtaR3 modulate the expression of target genes in association with various N-acyl-l-homoserine lactones (AHLs) as signaling molecules produced by the LuxI-type synthases BtaI1, BtaI2, and BtaI3. We have systematically dissected the complex QS circuitry of B. thailandensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 33 publications
6
46
0
Order By: Relevance
“…The ScmR transcriptional regulator was shown to influence the biosynthesis of C 8 -HSL, 3OHC 10 -HSL, and 3OHC 8 -HSL (26), the main AHLs produced by B. thailandensis E264 (10, 11, 13, 14). Therefore, we assumed that ScmR could intervene in the regulation of gene expression, inter alia , by impacting the QS-1, QS-2, and/or QS-3 systems of B. thailandensis E264.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ScmR transcriptional regulator was shown to influence the biosynthesis of C 8 -HSL, 3OHC 10 -HSL, and 3OHC 8 -HSL (26), the main AHLs produced by B. thailandensis E264 (10, 11, 13, 14). Therefore, we assumed that ScmR could intervene in the regulation of gene expression, inter alia , by impacting the QS-1, QS-2, and/or QS-3 systems of B. thailandensis E264.…”
Section: Resultsmentioning
confidence: 99%
“…While Mao et al (26) defined the ScmR regulon during the stationary phase, we established the impact of ScmR on the expression of genes during the logarithmic phase of growth. It must be emphasized that the growth stage is an important variable when investigating QS, and this is especially relevant for B. thailandensis , a bacterium for which we reported significant differences in QS regulation depending on the growth stage (11). We confirmed that ScmR is a global regulator of gene expression in B. thailandensis E264 (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The OD600 and relative luminescence were measured using a CLARIOstar plate reader at 10-minute intervals for 24 hours. Experiments assessing the effect of C8-HSL additions on CepR and CepI transcription were performed according to Le Guillouzer et al (88). Briefly, cultures were supplemented with C8-HSL (Sigma-Aldrich) resuspended in acetonitrile (10 µM final concentration) and added to cultures with acetonitrile added alone used as a negative control.…”
Section: Digestionmentioning
confidence: 99%